Cardiac transplantation in a 20-year-old woman with scleroderma. Issue 1 (February 2018) - Schreiber, Benjamin E; Parish, Victoria; Knight, Daniel S; Bell, Alexander D; Denton, Christopher P; Banner, Nicholas; Coghlan, Gerry
Purpose: To describe cardiac transplantation in a young woman with juvenile onset diffuse scleroderma and cardiac involvement. Methods: Case report. Results: A young White girl developed anti-topoisomerase-1 positive diffuse scleroderma aged 14 years with myositis. Pulmonary function tests were normal. Skin disease was treated with mycophenolate mofetil 1 g twice daily, methotrexate 7.5 mg weekly and periodic intravenous prostacyclin. When aged 17 years, she developed raised troponin T of 0.207 mcg/L (normal range <0.03) and NTproBNP (155 pmol/L); 6-min walking distance was 341 m, and she had episodes of presyncope with effort. The next year she developed symptomatic ventricular tachycardias and dual-chamber implantable cardioverter-defibrillator was inserted, with further episodes of ventricular tachycardia and one shock delivered. By age 19 years, 6-min walking distance was 125 m. Echocardiography showed ejection fraction of 15%–20% with dilated left ventricle and pericardial effusion. She was treated with intravenous Rituximab. She became breathless while dressing and managed only 118 m in 6 min. She experienced increasing orthopnoea and peripheral oedema and was found to be in a low cardiac output state, requiring treatment with intravenous milrinone to maintain renal function. She underwent orthotopic cardiac transplantation, making an excellent post-operative recovery, and was discharged 16 days later with tacrolimus, mycophenolate mofetil and prednisolone. After 1 year, she was in New York Heart Association functional class I and with normal cardiac function on echocardiography. Conclusion: This case illustrates the severe cardiac involvement that can occur in juvenile onset diffuse cutaneous systemic sclerosis, in which cardiac involvement is the leading cause of death.